The Zahir : a novel of obsession - Coelho, Paulo; Costa, Margaret Jull (New York : Harper Perennial, 2006)
A bestselling novelist finds himself trapped in a nightmare when his war correspondent wife, Esther, disappears with a man who may have been her lover.
Translation of: Zahir.
Booklist.
Library Journal.
Booklist, July 2005.
Library Journal, August 2005.
Adult
Keywords: Man-woman relationships -- Fiction; Missing persons -- Fiction; Novelists -- Fiction; Man-woman relationship -- Fiction; Missing persons -- Fiction; Novelists -- Fiction